2004
DOI: 10.1074/jbc.m403367200
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein Bam32 Regulates Rac1 Activation and Actin Remodeling through a Phosphorylation-dependent Mechanism

Abstract: The B cell adaptor molecule of 32 kDa (Bam32) is an adaptor that links the B cell antigen receptor (BCR) to ERK and JNK activation and ultimately to mitogenesis. After BCR cross-linking, Bam32 is recruited to the plasma membrane and accumulates within F-actin-rich membrane ruffles. Bam32 contains one Src homology 2 and one pleckstrin homology domain and is phosphorylated at a single site, tyrosine 139. To define the function of Bam32 in membrane-proximal signaling events, we established human B cell lines over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 57 publications
4
47
0
Order By: Relevance
“…One possible group is the Rho-family of GTPases such as Rac and Cdc42 which regulate a wide range of important cellular functions including actin polymerization, transcriptional activation, cell survival, and cell cycle entry (43). Interestingly, we found that Bam32 regulates BCR-induced activation of Rac1, suggesting that Bam32 regulates actin remodeling in B cells in part by a Rac-dependent mechanism (44). However, in contrast to a previous study (45), when we expressed a dominant-negative form of Rac1 in DT40 cells, we found that it had only a marginal effect on BCR internalization (data not shown).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…One possible group is the Rho-family of GTPases such as Rac and Cdc42 which regulate a wide range of important cellular functions including actin polymerization, transcriptional activation, cell survival, and cell cycle entry (43). Interestingly, we found that Bam32 regulates BCR-induced activation of Rac1, suggesting that Bam32 regulates actin remodeling in B cells in part by a Rac-dependent mechanism (44). However, in contrast to a previous study (45), when we expressed a dominant-negative form of Rac1 in DT40 cells, we found that it had only a marginal effect on BCR internalization (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…An important clue to defining the molecules involved in this process is the fact that Bam32 needs to be tyrosine phosphorylated to regulate BCR internalization. Indeed, BCR-induced actin polymerization is impaired in BJAB cells expressing a point mutant (Y139F) of Bam32 (44). It is possible that tyrosine phosphorylation of Bam32 causes a conformational change which in turn facilitates the interaction of Bam32 with actin-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bam32 is an adaptor protein that has been involved in Rac-mediated actin cytoske-leton remodeling at the cell membrane [45], suggesting that signaling-dependent cytoskeletal rearrangements are necessary for the internalization of more "complex" ligands (e.g. anti-IgM).…”
Section: Discussionmentioning
confidence: 99%
“…Bam32 phosphorylation by Src family kinases is also PI3K-dependent (17,22). Bam32 has been implicated in BCR signaling processes, including activation of the GTPase Rac1, and MAPKs ERK and JNK (23)(24)(25). Bam32-deficient B cells develop normally, but show markedly impaired BCR-triggered proliferation in vitro; however, proliferation could be fully recovered with addition of anti-CD40 and/or IL-4 stimuli (23,26).…”
mentioning
confidence: 99%